Effects of Lateral Heel Wedges and Lateral Forefoot Wedge on the Knee Adduction Moment in Healthy Male Students - Fatemeh Shamsi; Farhad Tabatabaei-Ghomsheh; Mahmoud Bahramizadeh; Seyyed Mohammad Ebrahim Mousavi; Pouria Rezasoltani (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: Lateral wedged insoles have been designed to decrease the force applied on the medial knee compartment. The aim of this study was to assess the effects of laterally wedged insoles regarding to the placement of the wedge under the sole (under the heel or under the forefoot) on the knee adduction moment and the ground reaction forces. Material & Methods: In this pretest-posttest study, three-dimensional gait analysis was performed on 20 healthy men between 18-30 years old. Knee adduction moment and ground reaction forces were compared among following three types of insoles: a flat insole, a 6˚ laterally inclined heel wedged insole and a 6˚ laterally- inclined forefoot wedged insole. Results: there was no difference between three conditions (flat insole (9.72±1.501), lateral heel wedge (9.866±2.141) and lateral forefoot wedge (9.952±1.986) in peak knee adduction moment (P>0.05). Ground reaction forces and spatiotemporal parameters of gait were not affected by any types of these insoles (P>0.05). Conclusion: Based on the current finding, placement of the lateral wedge under the sole, that is, under the heel or under the forefoot has no effect on the efficacy of these insoles on the adduction moment of the knee and ground reaction forces.